ANTIBACTERIAL ACTIVITY OF ETHANOL EXTRACT OF RED ANDONG LEAVES (Cordyline fruticosa (L.) A.Chev.) AGAINST Bacillus cereus FNCC-0059 - Elisabeth Oriana Jawa La; Ni Putu Prasintia Dewi; Repining Tiyas Sawiji; Ni Ketut Esati; Mahadri Dhrik (Pharmacy Department, Math and Sciences Faculty, Udayana Univerity, 2026)
Introduction: Cordyline fruticosa (L.) A.Chev. (red andong) has long been utilised in traditional ethnopharmacological practices by several indigenous communities, including the Dayak and Tolaki Mekongga tribes. The leaves are reported to contain various bioactive secondary metabolites, including flavonoids, tannins, saponins, and triterpenoids, which are associated with antibacterial activity. Objective: This study aims to identify the phytochemical content and antibacterial activity of the ethanol extract of red andong leaves (Cordyline fruticosa (L.) A. Chev.) against Bacillus cereus. Methods: This laboratory experimental study involved plant identification, sample collection, ethanol maceration extraction, phytochemical screening, and evaluation of antibacterial activity. Antibacterial activity against B. cereus was determined using the agar well diffusion method. The ethanolic leaf extract was tested at concentrations of 30%, 60%, and 90%, with azithromycin 1% serving as the positive control and water for injection as the negative control. Results: Phytochemical screening of red andong leaf extract showed positive results for flavonoids, saponins, tannins, phenols, and triterpenoids. Red andong leaf extract had antibacterial activity against Bacillus cereus at concentrations of 30%, 60%, and 90%. Mann-Whitney analysis showed that all concentrations were significantly different from the negative control (p≤0.05), but there was no significant difference between concentrations. Conclusion: The ethanol extract of red andong leaves positively contained flavonoids, saponins, tannins, phenols, and triterpenoids. Cordyline fruticosa (L.) A.Chev. Leaf extract has antibacterial activity against Bacillus cereus FNCC-0059, with moderate to strong inhibition. Keywords: Cordyline fruticosa (L.) A.Chev.; Bacillus cereus; antibacterial activity; agar well diffusion method; phytochemical screening